The application of dynamic pressure sensor based on fiber Bragg grating for monitoring of water supply system - Hafizi, Z. M.; Yusof, Mohd Fadhlan M.; Ghazali, M. F.; Sani, M. S.M. (2016)
In this work, a diaphragm type of fibre Bragg grating dynamic pressure transducer was successfully designed and developed. The proposed design of the transducer utilized a thin metal diaphragm, acted as a primary sensing element, and integrated with an FBG sensor acts as a secondary sensing element. Prior to the fabrication of the transducer, Autodesks Mechanical Simulation software was used for finite element analysis. Several experiment schemes were carefully planned and conducted to study the static and dynamic response of the FBG sensor. For static experimentation, an air compressor was used to pressurize a metallic pipe test rig. The FBG sensor then detected the applied inner pressure indirectly as both static and dynamic sensor. During the application of pressure to the test rig, the deformation of the diaphragm causing the FBG sensor to stretched or compressed along its length. As consequence, this causes variation in Bragg wavelength; whereby its reflected spectra can be observed using an Optical Spectrum Analyser (OSA). Once the sensitivity of the spectra changes was verified, a matched edge FBG interrogation system was then replaced the OSA, in order to convert the optical signal into electrical signal. A reliability test to the FBG pressure transducer has proven the capability of the transducer for a robust pressure measurement, whereby the results indicated sensitivity of 106 pm/bar. In addition, the FBG sensor also has an excellent linearity with a fitting linear correlation coefficient of 99.91% in pressure measurement. From the repeatability test, an error is found to be less than 0.3%.